2006
DOI: 10.1108/02683940610684418
|View full text |Cite
|
Sign up to set email alerts
|

Fear in organizations

Abstract: PurposeThis study examines the relationship between interactional justice, which is a specific type of organizational justice perception that reflects how a person is treated by an authority, and workplace internet deviance (or Cyberloafing) as a category of deviant workplace behavior. The tested model suggests that interactional justice affects cyberloafing by influencing fear of formal punishment –as an intimidation construct– which, in turn, prompts employees to reciprocate with deviant workplace internet b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…We also highlight that employee and employer definitions and measures of PWU may not necessarily be the same. Current scholarly explanations on what influences PWU appear to rest on the assumption that self-reported and EM-reported PWU frequencies are comparable (e.g., Blanchard & Henle, 2008;Eastin, Glynn & Griffiths, 2007;Lee, Lee & Kim, 2004;Lim, 2002;Mahatanankoon, Anandarajan & Igbaria, 2004;Manrique De Lara, 2006;Shaw & Gant, 2002). We found that the two measures of PWU (self-reported access or try to access and EM-reported blocking of attempted access) are not identical.…”
Section: Limitations and Opportunitiesmentioning
confidence: 56%
“…We also highlight that employee and employer definitions and measures of PWU may not necessarily be the same. Current scholarly explanations on what influences PWU appear to rest on the assumption that self-reported and EM-reported PWU frequencies are comparable (e.g., Blanchard & Henle, 2008;Eastin, Glynn & Griffiths, 2007;Lee, Lee & Kim, 2004;Lim, 2002;Mahatanankoon, Anandarajan & Igbaria, 2004;Manrique De Lara, 2006;Shaw & Gant, 2002). We found that the two measures of PWU (self-reported access or try to access and EM-reported blocking of attempted access) are not identical.…”
Section: Limitations and Opportunitiesmentioning
confidence: 56%
“…In negative PUTW studies, scholars have primarily discussed deterrence-based policies for curbing PUTW, such as internet monitoring and sanctions. Although some of the findings are mixed (Chen et al, 2008;Rahimnia & Mazidi, 2015;Zoghbi-Manrique-de-Lara, 2006), these studies have generally found that monitoring and sanctions are useful for mitigating PUTW (Glassman et al, 2015;Henle et al, 2009;Shepherd et al, 2014;Ugrin & Pearson, 2013Urbaczewski & Jessup, 2002;Wang et al, 2013), especially when internet monitoring and sanctions are combined together (Zoghbi-Manrique-de-Lara & Olivares-Mesa, 2010). Deterrence-based policies can curb PUTW because monitoring and sanctions can increase employees' perceived risk of engaging in PUTW.…”
Section: Putw Policies: Deterrence or Non-deterrencementioning
confidence: 99%
“…On the one hand, deterrence-related factors are less salient in explaining PUTW than other factors, such as the perceived benefits of PUTW and personal norms against PUTW (Li Moody & Siponen, 2013). On the other hand, deterrence policies may elicit employees' resistance, such as increased PUTW behaviour (Wang et al, 2013;Zoghbi-Manrique-de-Lara et al, 2006) and decreased job satisfaction (Jiang et al, 2020;Shepherd & Klein, 2012;Urbaczewski & Jessup, 2002). Accordingly, these studies have discussed PUTW policies that are less coercive (Ivarsson & Larsson, 2011).…”
Section: Putw Policies: Deterrence or Non-deterrencementioning
confidence: 99%
“…Research on emotion in conflict situations has repeatedly demonstrated that negotiators experiencing positive emotions are more cooperative and agreeable, whereas those Moderated mediation approach experiencing negative affect tend to be more competitive and aggressive (Allred et al, 1997;Baron, 1990;Forgas, 1998;Laslo-Roth and Schwarzwald, 2016;Pillutla and Murnighan, 1996). To a lesser extent, research has shown that negative emotions (such as fear of punishment) can cause more compliance (Brooks and Schweitzer, 2011;Zoghbi Manrique de Lara, 2006). These contradictory findings may stem from a poor distinction between the different negative emotions expressed (anger vs sadness) or from the existence of a moderating factor such as emotion regulation.…”
Section: Emotional Regulation and Compliancementioning
confidence: 99%